2015
DOI: 10.1007/s12032-015-0484-3
|View full text |Cite
|
Sign up to set email alerts
|

The implications and mechanisms of the extra-nuclear nucleolin in the esophageal squamous cell carcinomas

Abstract: In recent decades, the multi-functional protein nucleolin (NCL) has been reported to express outside the nucleus of many cancer cells. However, the expression and role of the extra-nuclear NCL in esophageal squamous cell carcinoma (ESCC) were not well characterized. Here, NCL was detected by immunohistochemistry and Western blotting in 60 ESCC tissues. Further, the associations of NCL, EGFR, CXCR4 and Ki67 were analyzed by in vitro assays. Our results showed that NCL expression in all 40 cases of ESCC tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 21 publications
5
18
0
Order By: Relevance
“…levels of nucleolin/P-nucleolin expression. These are results are consistent with those of previous studies (24,25).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…levels of nucleolin/P-nucleolin expression. These are results are consistent with those of previous studies (24,25).…”
Section: Discussionsupporting
confidence: 94%
“…Nucleolin is detectable in cancer cells and is involved in the development of cancer. It has also been associated with poor prognosis for a variety of types of cancer (24,25). For example, nucleolin inhibits P53 and enhances Bcl-2 and protein kinase B (Akt) expression to promote the proliferation of human glioma cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular location of the protein reflected differences in the patient's prognosis, where high cytoplasmic staining was associated with a significant recurrence rate and shortened survival rate (log-rank p < 0.0001) 253 . Similar results were reported for esophageal squamous cell carcinomas, in which extra-nuclear expression of nucleolin was significantly correlated with metastatic disease and associated with poor overall survival (log-rank p < 0.000) 469 . Nevertheless, the pattern of nucleolin staining associated with malignancy and cancer progression is not the same for other types of tumors.…”
Section: Introductionsupporting
confidence: 84%
“…Recent studies have also reported nucleolin overexpression in human-derived tumor tissues as an unfavorable predictor, related to a higher risk of recurrence and worse overall survival of patients, in a variety of neoplasias 253,256,257,259,467,468 . Moreover, the predictive power of nucleolin in a pattern-dependent manner was shown for some types of neoplasias 251,253,254,257,469 . In gastric tumors, both nucleolar and cytoplasmic nucleolin staining was observed, while only nucleolar staining was identified in non-malignant tissues.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, in some types of malignant tumors, extranuclear cytoplasmic nucleolin has been shown to correlate with poor prognosis. A similar pattern has been found in lung and esophagus cancers [Qi et al 2015;Xu et al 2016]. Nucleolin has also been shown to play an important role in breast tumors (Moura et al 2012) and to be even associated with tumor angiogenesis [Christian et al 2003].…”
Section: Introductionsupporting
confidence: 70%